Improving the Active Participation of Grade X Students at SMA PGRI 1 Padang Through the Use of Chemical Element Card Media - Mentari Az Zahra; Yerimadesi Yerimadesi; Friyatmi Friyatmi; Jasniar Jasniar (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
Active participation of students is one of the important aspects in improving the understanding of chemical concepts. This research is a Classroom Action Research that aims to increase the active participation of students in class X SMA PGRI 1 Padang through chemical element card media on electron configuration material and periodic table of elements. This research was conducted in two cycles which included the stages of planning, action implementation, observation, and reflection. Data were collected using observation sheets with physical and psychological indicators. The results showed an increase in students' active participation from 64.42% in cycle I to 86.95% in cycle II. Rewards proved to be effective in increasing students' active participation